2012
DOI: 10.1074/mcp.m112.020164
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces of Proteasome-catalyzed Peptide Splicing in Yeast and Humans

Abstract: Proteasome-catalyzed peptide splicing (PCPS) represents an additional activity of mammalian 20S proteasomes recently identified in connection with antigen presentation. We show here that PCPS is not restricted to mammalians but that it is also a feature of yeast 20S proteasomes catalyzed by all three active site ␤ subunits. No major differences in splicing efficiency exist between human 20S standard-and immuno-proteasome or yeast 20S proteasome. Using H 2 18 O to monitor the splicing reaction we also demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
179
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(196 citation statements)
references
References 29 publications
14
179
3
Order By: Relevance
“…However, we did not detect a clear impact of polypeptide length on the degradation rate by 20S proteasomes in agreement with our previous observation (Mishto et al 2008) and the degradation rates of polypeptides with similar length but different sequence, such as pp89 and gp100 , were differently affected by the age of the animals. Previously, we have also shown that the impact of the six proteasomal catalytic sites varies between these latter substrates (Mishto et al 2012). These two facts suggest that rather the sequence than the length of the substrate polypeptides is the reason for the agedependent differences in proteasomal degradation rate.…”
Section: Discussionmentioning
confidence: 93%
“…However, we did not detect a clear impact of polypeptide length on the degradation rate by 20S proteasomes in agreement with our previous observation (Mishto et al 2008) and the degradation rates of polypeptides with similar length but different sequence, such as pp89 and gp100 , were differently affected by the age of the animals. Previously, we have also shown that the impact of the six proteasomal catalytic sites varies between these latter substrates (Mishto et al 2012). These two facts suggest that rather the sequence than the length of the substrate polypeptides is the reason for the agedependent differences in proteasomal degradation rate.…”
Section: Discussionmentioning
confidence: 93%
“….S n depending on their proximity to the scissile peptide bond, and C-terminal ligation partners that may fit the primed proteasomal pockets S 1 9, S 2 9, S 3 9. . .S n 9, but have also been postulated to bind to a distinct proteasomal splicing product binding site (11). Amino acid residues in both ligation partners that interact with these proteasomal substrate binding pockets are here referred to as P 1 , P 2 , P 3 .…”
Section: Distinct Peptide Motifs Either Promote or Abolish Ag Splicingmentioning
confidence: 99%
“…Because spliced Ags may mediate T cell responses to cancer, transplants, and viral infection, predicting their generation would be important for the development of vaccines and immunotherapies or to pharmacologically suppress T cell responses (12). Although proteasomal peptide ligation can readily be detected in vitro (11,15), identifying spliced Ags in vivo has proven to be difficult with only five immunomodulatory spliced epitopes identified (5)(6)(7)(8)(9). Classically, novel epitopes are identified by cell surface elution and mass spectroscopy (MS) analysis, followed by matching against protein databases (16,17).…”
mentioning
confidence: 99%
See 2 more Smart Citations